Dual targeting of the PI3K/Akt/mTOR pathway as an antitumor strategy in Waldenstrom macroglobulinemia - Roccaro, Aldo Maria; Sacco, Antonio; Pitsillides, Costas; Husu, Emanuel; Vesole, Steven; Azab, Abdel Kareem; Azab, Feda; Melhem, Molly R.; Ngo, Hai T.; Quang, Phong; Maiso, Patricia; Runnels, Judith M.; et al. (My University, 2010)
We have previously shown clinical activity of a mammalian target of rapamycin (mTOR) complex 1 inhibitor in Waldenstrom macroglobulinemia (WM). However, 50% of patients did not respond to therapy. We therefore examined mechanisms of activation of the phosphoinositide 3-kinase (PI3K)/Akt/mTOR in WM, and mechanisms of overcoming resistance to therapy. We first demonstrated that primary WM cells show constitutive activation of the PI3K/Akt pathway, supported by decreased expression of phosphate and tensin homolog tumor suppressor gene (PTEN) at the gene and protein levels, together with constitutive activation of Akt and mTOR. We illustrated that dual targeting of the PI3K/mTOR pathway by the novel inhibitor NVP-BEZ235 showed higher cytotoxicity on WM cells compared with inhibition of the PI3K or mTOR pathways alone. In addition, NVPBEZ235 inhibited both rictor and raptor, thus abrogating the rictor-induced Akt phosphorylation. NVP-BEZ235 also induced significant cytotoxicity in WM cells in a caspase-dependent and -independent manner, through targeting the Forkhead box transcription factors. In addition, NVPBEZ235 targeted WM cells in the context of bone marrow microenvironment, leading to significant inhibition of migration, adhesion in vitro, and homing in vivo. These studies therefore show that dual targeting of the PI3K/mTOR pathway is a better modality of targeted therapy for tumors that harbor activation of the PI3K/mTOR signaling cascade, such as WM
Keywords: Waldenstrom Macroglobulinemia; Immunoglobulin M; WM patients